PENERAPAN ROLE PLAYING MENINGKATKAN PEMAHAMAN PENDIDIKAN AGAMA ISLAM TENTANG SALAT FARDU KELAS III SD - M.YASIN (Madani Institute | Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2013)
The use of the method Playing Role ( Role Playing ) is a proposed solution to improve learning outcomes Islamic Education ( PAI ) in the third grade students of SDN 19 East Cengkareng West Jakarta evening . This study was conducted in two cycles , with details of the preparation of the first and second cycles as follows: ( 1 ) Make a plan that makes learning devices ( RPP - 1 , interview guides , test questions, KBM teacher assessment ) , ( 2 ) action ( KBM teacher in class ) , ( 3 ) observation ( assessment by kolaboarator for KBM ) and ( 4 ) Reflection , discusses the advantages and disadvantages for teaching and learning between teacher educators and collaborators . Data obtained from formative tests , student interviews and assessment collaborator / observer . Second cycle executed as in the first cycle with a different material . From the research data obtained by the increase of PBM cycle of learning outcomes 1 , namely the class average 60.90 . These results no increase in the average value when compared to pre- cycle obtain the average value of 52.20 . Similarly, the number of students who are able to master the material above SKBM ( 70 % ) at the end of cycle 2 number of 20 students or 60.00 % . Average grades in cycle 2, there was an increase from the first cycle that becomes 70.30 . Based on the data obtained from the results of this study , proves that by applying the method of playing a role ( role playing) , has been able to improve students' understanding of Islamic Religious Education ( PAI ) in the third grade students of SDN 19 East Cengkareng West Jakarta evening . Although these results have not reached the expectations that have been determined , because of some of the students' learning activities remains largely below 70 %.